New marine low trophic resources as food: nutritional and food safety aspects - Elvevoll, Edel Oddny; Eilertsen, Karl-Erik; Aschan, Michaela; Bandarra, Narcisa Maria (Frontiers in Aquaculture, 2023)
Food agencies recommend increased consumption of aquatic food in the diet to promote healthy living and sustainability, particularly to prevent Western lifestyle-related diseases and secure sustainable food systems. This requires growth in global seafood production, and the utilization of low trophic species (LTS) is suggested. LTS are already considered nutritious and important in Asian and Pacific diets. As the use of LTS is expanding in Western diets, producers and consumers need information on food safety and nutritional contribution. LTS are mainly immobile or slow-moving extractive species or organisms feeding on such, and their nutrient and contaminant content varies by species and location. Species-specific knowledge on nutritional contents and safe consumption limits are often missing, making monitoring and analysis of contaminants, nutrients, and consumption data crucial to guide the utilization and consumption of LTS. Using global and regional standards regarding nutrients, food hazards, and labeling, this review highlights appropriate guidelines and regulations to guide the utilization of selected novel species and identifies knowledge gaps.